Acceptability, Usability, and Effectiveness: A Qualitative Study Evaluating a Pediatric Telemedicine Program - Sauers-Ford, Hadley S. (Acad Emerg Med, 2019)
BACKGROUND: Pediatric emergency telemedicine consultations have been shown to provide support to community emergency departments treating critically ill pediatric patients. However, despite the recognized value of telemedicine, adoption has been slow. To determine why clinicians frequently do not use telemedicine when it is available for pediatric patients, as well as to learn how to improve telemedicine programs, we conducted a qualitative study using stakeholder interviews. METHODS: We conducted a qualitative study using grounded theory methodology, with in-depth interviews of referring and accepting physicians and referring, transport, and transfer center nurses. We analyzed data iteratively and adapted the interview guide based on early interviews. We solicited feedback from the participants on the conceptual model. RESULTS: Sixteen interviews were conducted; all respondents had been involved in a telemedicine consultation at least five times, with some having used telemedicine more than 30 times. Analysis resulted in three themes: (1) Recognizing and addressing telemedicine biases are central to gaining buy-in, (2) As technology advances, telemedicine processes need to adapt accordingly, and (3) Telemedicine increases collaboration among health care providers and patients/families in the patient care process. CONCLUSIONS: To improve patient care through increased use of telemedicine for pediatric emergency consultations, processes need to be modified to address provider biases and end-user concerns. Processes should be adapted to allow users to utilize a variety of technologies (including smartphones) and to enable more users, such as nurses, to participate. Finally, telemedicine can be used to improve the patient and family experience by including them in consultations.